Biomedical and social constructions of menopause - Serrano, Jerome Alterado; Natividad, Josefina N.; Serrano, Jerome Alterado (Quezon City College of Social Sciences and Philosophy, University of the Philippines Diliman, 2001)
This paper draws on data collected from a barangay-based research utilizing a survey and focus-group discussion (FGD) sessions conducted in Davao City, Philippines in 1998-1999 and highlights the distinctive (and often, competing) manner by which menopause is represented by biomedicine and by women in the context of their social and cultural realities. The biomedical construction of menopause emphasizes the centrality of physiological processes in understanding this particular life event among women and this kind of formulation essentially leads to empirical analysis of symptom incidence as well as the relevant characteristics of women and their attitudes towards menstrual cessation. These are conceptually illustrated to have mitigating effects on symptom recognition and consequent health-seeking patterns among the sample of women in this study. Consistent with biomedicine's formulation of the human body as a "desocialized" and "mechanistic" entity capable of being clinically investigated, the physiological referents of menopause have been consistently interpreted as pathological condition requiring medical treatment. For many women in this study however, menopause has been considered as only one of those aspects of their womanhood which is generally welcomed and accepted as a natural sign of aging. Most women in this study dynamically locate their experience of menopause in relation to their menstruation, their everyday practice as a worker, a wife, a mother, and these, in turn, enable them to interpret this life stage and make sense of it in a manner that is deeply reflective of their social and cultural milieu. Through the exploration of the "social embeddedness" of the physiological basis of menopause, the paper stresses the fluidity and heterogeneity of the knowledge forms relevant to this life event as well as cultural system that mediates and shapes such knowledge forms. This essential in order to develop a more ethically sensible reflections about the life processes of women which are in the constant threat of being medicalized , the most recent of them in menopause.
Thesis (Master of Arts in Sociology)--University of the Philippines Diliman
Keywords: Menopause; Menopause--Public opinion; Menopause -- Davao City -- Philippines